Rice-Based Farming Systems and Its Diversification:An Economic Analysis in Coastal Ecologies of Eastern India - Behera, U. K.; Giri, Ajit; Mishra, Arun Kumar; Bhargavi, B.; Kar, Ashok; Pal, Gangadhar (Indian Journal of Hill Farming, 2018)
For understanding the role of different types of farming systems on the livelihoods of small and marginal farmers, a study was made under eastern Indian situations during 2015- 16 comprising around 100 farming systems. The study revealed that rice - fallow and ricerice system in the region can be made profitable and sustainable through introduction of legume crop. Integrated farming systems (IFS) are important for the efficient management of available resources at the farm level to generate adequate income and employment for the rural poor, for the promotion of sustainable agriculture, and for the protection of the environment. The synergistic interactions of the components of integrated farming systems need to be explored to enhance resource use efficiency and recycling of farm by-products. IFS has proved to be the boon to the small and marginal farmers by providing regular income of about Rs. 500/day/ha, thus playing a vital role in improving and stabilizing the farmers economy. Such farm proved to be climate resilient in nature and a better strategy for climate change adaptation and mitigation. Promotion of integrated farming systems can be a vital strategy for developing climate resilient technology and improving the livelihood of small and marginal farmers in the region.